Checking the condition of the shutter in the water distribution system using a laser sensor - Jumaniyozov, Z.G.; Yarashov, I.K. (Science and Education, 2023)
Laser water distribution is one of the sensors we need to control mechatronic modules. Based on the information coming from it through this sensor, it performs the control function of raising and lowering the gates in the water distribution mechatronic modules to a certain distance and includes the tasks of always showing the status of the gates.